The impact of online gaming on psychological and social well-being among college students in Brunei Darussalam - Mahalle, Salwa; Zailani, Fifi Faulina (Jurnal Cakrawala Pendidikan, 2025)
Online gaming is becoming popular among teenagers as adults. The impacts of playing games may be positive or negative. Hence, the research aims to determine the impacts of online gaming on one's social and psychological well-being, specifically in terms of how online gaming affects students' social integration and social interactions and how online gaming is related to depression. The participants in this study are 180 college students, and data was analysed quantitatively. The findings revealed that among the college students, the majority identified as explorers (33%), followed by achievers (30%), killers (24%), and socializers (13%). The study indicated that while moderate gaming can enhance social integration, excessive gaming is linked to increased feelings of loneliness and depression. Students who spent less than three hours gaming maintained their real-life social relationships, suggesting that controlled gaming can coexist with healthy social interactions. Conversely, those who experienced feelings of loneliness in-game were more likely to report depressive symptoms, highlighting the importance of social support in mitigating negative psychological outcomes. In conclusion, online gaming does not inherently harm social and psychological well-being; rather, gaming time management and the nature of social interactions determine its impact. Recommendations include promoting awareness of mental health issues related to gaming and encouraging students to seek support when needed.